Hubungan Dukungan Keluarga Dengan Tingkat Depresi Pada Pasien Diabetes Melitus Tipe II Di Rumah Sakit Imelda Medan - Ribka Herni S. Gea; Rostime H. Simanullang (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Family support is the most important part of a family. Family support has a good impact on health and the patient's recovery. Without family support, it will be low cure rate. Depression is a personality disorder characterized by a constant mood of feeling sad, empty, irritable, along with certain cognitive and somatic symptoms. Objective: To examine the relationship between family support and depression levels in type II DM patients at Imelda Hospital Medan. Methods: This type of research is quantitative with a correlational approach. Sampling used cross sectional sampling of 70 respondents. Data analysis used the Spearman's rho correlation test. Results: The results of this study showed that there was a significant relationship between family support and depression rate with a p-value of 0.00<0.05 and a correlation coefficient of -0.477. Conclusion: There is a significant relationship between family support and depression rates in type 2 diabetes mellitus patients at Imelda Hospital Medan and both have a negative relationship where if family support is high, the depression rate is low or vice versa. For further research, it is hoped that other variables will be added, such as factors for fulfilling the spiritual needs of guided imagery, as well as using other research methods.